TINJAUAN TERHADAP UNSUR KO-KREASI DALAM PAMERAN PROJEK MONYET@USM = A REVIEW OF CO-CREATION ELEMENT IN PROJECT MONKEY@USM EXHIBITION - Mohamad Faizuan, Mat; Hasnul Jamal, Saidon (Faculty of Humanities, Arts and Heritage, Universiti Malaysia Sabah., 2022)
The Project Monyet@USM exhibition was held for the first time at the Muzium Galeri Tuanku Fauziah, Universiti Sains Malaysia (USM) from 25 October 2021 until 15 January 2022. The exhibition was curated by Hasnul Jamal Saidon and Afzanizam M.Ali. The exhibition does not feature leading artists or professional art practitioners. Instead, the exhibition incorporates some elements of co-creation with the cooperation of various parties. In particular, the involvement of the public members who were invited to contribute their artworks related to the subject of the exhibition. This article discusses the use of co-creation methods as part of its curatorial strategy.